Emergent issues In heterodox Islam among the Yoruba of Nigeria - Saheed Ahmad Rufai, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
The field of Islamic Studies is currently witnessing the growth of a sophisticated body of scholarship on “orthodoxy and heterodoxy” in Islamic religious practices. Such a growing scholarship has largely promoted the perception that heterodox Islam otherwise known as local Islam, popular Islam, people’s Islam or cultural Islam, is not the same as orthodox Islam, which is assumed as real, pure, right, official or revealed Islam. Such a perception lends credence to the impression that the dimension of Islamic religious practices in any setting is supposed to be negotiated and determined by the adherents of Islam in such a setting and not by external factors or considerations. The purpose of this article is to examine the continued spread of heterodox Islam among the Yoruba people of Southwestern Nigeria. The article seeks to identify and analyze the factors instrumental to the growing influence of heterodoxy on orthodoxy, and offer practical recommendations for possible purification of Yoruba Islam from traditional, heretical, heterodox or non-Islamic practices.